Sleep Quality Among Undergraduates During Pre-Examination Period - Aishah Ahad, Nor (Indonesian Journal of Education Methods Development, 2019)
The purpose of the study is to examine the sleep quality of undergraduates during pre-examination period. In addition, the effect of examination stress and sleep quality on academic performance of the undergraduates is also of interest. Questionnaire is used to collect responses from 379 undergraduates regarding perceived stress and sleep quality on the first week of final examination. Pittsburgh Sleep Quality Index (PSQI) is the instruments used in investigating the perceived sleep quality of respondents one month before the test is taken. Perceived Stress Scale (PSS) is used to measure the perceived stress level of the subjects for the past one month. The data dissemination concludes that the overall sleep quality of the undergraduates is poor. Female undergraduates tend to have a slightly better sleep quality than the male undergraduates. The sleep quality shows a weak positive relationship with perceived stress. It is also discovered that sleep quality and perceived stress have no effect on academic performance. The university authority might need to look into the problem of poor sleep quality among undergraduates especially during pre-examination period.